METHODS OF PREVENTING VIOLENCE ON CHILDREN IN THE FAMILY IN TELEPHONE COUNSELING - N. Tokareva (Вестник Мининского университета, 2017)
In article considered the main goals and objectives of the «Helpline Telephone», the motivations of children and adults that appeal to "Helpline Telephone" and the main problems faced by parents and children, contact the «Helpline Telephone». In article analyzes the methods of work of the center and on the basis of the analysis make performance criteria of «Helpline Telephone» work.